A STUDY ON THE EXTRACTION PROCESS OF ACTIVE INGREDIENTS FROM AKEBIA STEM AND AN ANALYSIS OF THEIR ANTI-GASTRIC CANCER ACTIVITY - Lu, Yi-Zhuo; Ye, Hui-Ming; Zeng, Hua-zong; Li, Liang-Hui; Wu, Guo-Yang; Liu, Guo-Yan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The study investigated the extraction process of active ingredients from akebia stem and an analysis of their anti-gastric cancer activity. Three different extraction methods were used to obtain extracts, namely the decoction method (group A), reflux extraction method (group B), and maceration method (group C), of which reflux extraction method and maceration method used ethanol as the extraction solvent, while decoction method used distilled water for extraction. The differences in anti-gastric cancer activity of the three extracts were compared. MTT assay was used to test and compare the inhibitory effects of extracts obtained in A, B, and C groups on gastric cancer cells. The results showed that the dry extract obtained by heat reflux extraction with “water-ethanol” ratio of 1:2, extractant volume of 70 ml, with ethanol as extraction solvent presented the best inhibitory activity on gastric cancer SGC-7901 cells in this study. Its inhibitory effect did not change over time, and was directly proportional to the concentration.